Konsep Diri, Konformitas dan Perilaku Konsumtif pada Remaja - Suminar, Eva; Meiyuntari, Tatik (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2015)
Abstract. . The purpose of this study is to examine the correlation between self-conceptand conformity with adolescent consumer behavior. Research variables were measuredusing a consumer behavior scale, self concept scale and conformity scale. Subjects were60 students at 2nd grade SMA Darut Taqwa Pasuruan. Data were analyzed usingregression analysis. The results showed that self-concept and conformity significantlyassociated with consumer behavior. Separately, self-concept significantly has a negativecorrelation with consumer behavior. Meanwhile, conformity did not correlatesignificantly with consumer behavior.Keywords: Consumer behavior, Self concept, Conformity, Adolescent